CONCREEP 10 : Mechanics and Physics of Creep, Shrinkage, and Durability of Concrete and Concrete Structures : Proceedings of the 10th International Conference on Creep, Shrinkage, and Durability of Concrete and Concrete Structures, September 21-23, 2015 Vienna, Austria - Hellmich, Christian, 1971-; Pichler, Bernhard; Kollegger, Johann (American Society of Civil Engineers, 2015)
This collection contains 187 papers invited on the basis of carefully peer-reviewed abstracts. It elucidates the intricacies of concrete, linking atomistic physics to real life civil engineering design. Topics include: microstructures and micromechanics; multiscale creep, shrinkage, fracture, and durability properties; constitutive and numerical modeling; simulation and design of concrete structures; molecular- to lab-scale simulations and characterization of concrete; macroscopic material testing; creep and shrinkage of concrete under extreme conditions; monitoring of concrete structures and exploitation of measurement data; and creep and shrinkage properties of new cementitious materials. Scientists from physics and engineering disciplines working on the next generation of materials will find that these papers present the state-of-the-art in concrete creep, shrinkage, and durability mechanics. -- Provided by publisher.
Keywords: Concrete -- Creep -- Congresses.; Concrete -- Expansion and contraction -- Congresses.; elektronické knihy; electronic books